Gambaran Tingkat Kecemasan Dengan Nilai Ujian Pada Mahasiswa Angkatan 2021 Fakultas Kedokteran Ukrida Jakarta Tahun 2024 - Saputra, Roy; Hartono, Budiman; Osya Farfar, Inggrid (Universitas Kristen Krida Wacana, 2025)
Faculty of Medicine students spend more time of education than other faculties students, so it is more demanding academically and emotionally and are known to experience a fairly high incidence of psychological distress. This distress has an impact on academic performance and confidence of the students. This study aims to find out the overview of anxiety with exam grades experienced by students of the Faculty of Medicine class of 2021. This study uses a descriptive observational method. Primary data was obtained from a questionnaire with the Hamilton Anxiety Rating scale, with the number of samples required amounting to 59 respondents who met the inclusion and exclusion criteria. Based on the data obtained, the majority of respindents prepared themselves the day before the exam, in the first and second exams, the majority of respondents did not experience anxiety, but at the same time, the failure rate was more than 50% with the main factor of anxiety being the exam materials that were too difficult and/or lack of time to study. There has been an increase in grades from the first, second and the herr of Integration exams. In the Skills Lab Exam, 71% respondents did not experience anxiety with failure rate of 5% of the total respondents, with the main factor of anxiety being the examiner factor. It was concluded in this study that anxiety did not have a significant impact on the exam results.